Portable and wireless imaging of dorsal hand vein - See, Hui Ern; Huong, Audrey; Wan Mahmud, Wan Mahani Hafiza; Ngu, Xavier (Institute of Advanced Engineering and Science, 2020)
Technologies for visualization of dorsal hand vein are of the great interest in the studies of drugs-body response, identity authentication and human metabolism. This study integrates near infrared (NIR) technology into an optical system for non-contact, mobile and quick on the spot visualization of dorsal vascular system. The performance of the developed system was tested on twenty subjects of different skin tone and body frame dimensions. The results showed that the proposed system is able to produce output image of Signal-Noise Ratio (SNR) and Peak SNR of greater than 30 dB and 20 dB, respectively. While this work found a correlation between skin tone and image quality metrics, high consistency was observed in the quality metrics calculated for image data of individuals having different body frame size. This work concluded that the proposed system can be suitably used as a portable and robust tool for enhanced visualization of dorsal hand vein.